The Soros lectures : at the Central European University - George Soros. (PublicAffairs, 2010)
Includes index, p. 121-127. Five lectures delivered at the Central European University in Budapest, Oct. 26-30, 2009. Contents: The human uncertainty principle -- Financial markets -- Open society -- Capitalism versus open society -- The way ahead.